"A Disease of the Outside People": Native American Men's Perceptions of Intimate Partner Violence. (March 2015) - Matamonasa-Bennett, Arieahn
Intimate partner violence (IPV) has been identified as one of the most serious issues facing Native American women. Despite epidemic rates of IPV in urban and reservation communities, less is known about IPV in Native American populations than with any other racial group, and the existing literature and intervention research are scant. Many Native American scholars assert that IPV was rare and severely sanctioned in pre-contact societies. The present community-level, qualitative study used ethnographic and grounded theory approaches to examine the beliefs and perspectives of nine men from a Great Lakes reservation community who had experiences with IPV. These men believed that IPV was an increasing problem in the community and that it was not a part of traditional pre-contact culture but instead is a problem brought on by colonization and the introduction of alcohol. They indicated that returning to traditional tribal values was key to sobriety and nonviolence. Study themes suggest the importance of the historical social context and Native cultural values as essential elements in prevention and treatment initiatives. The study supports current Native American approaches to IPV and the ecological feminist framework for understanding violence against women. The article concludes with suggestions for culturally sensitive approaches for future research in Native American communities.